2017
DOI: 10.5433/1679-0359.2017v38n2p607
|View full text |Cite
|
Sign up to set email alerts
|

Granulometric and oxidizable carbon fractions of soil organic matter in crop-livestock integration systems

Abstract: The identification of the labile and recalcitrant forms of soil organic matter (SOM) allows to rapidly define, or even predict if the management used favors increments or losses of carbon in the soil. Thus, the objective of this work was to assess the effects of different grazing intensities and soybean crops on the oxidizable and granulometric fractions of the SOM in a crop-livestock integration combined with no-tillage system (CLI-NTS), established in 2009 in the Goiás Federal University. The treatments cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The changes in some of these attributes may be related to crop residues, that is, from maize (straw) and pasture (forage mass), and residues from the excreta of grazing animals. Studies have reported the effect of these residues on soil (Bieluczyk et al, 2017; Carvalho et al, 2009; Deiss et al, 2016; Garcia et al, 2008; Silva et al, 2014; Zhou et al, 2020) but few of them have investigated the importance of sowing techniques for the implementation of ICLS in an Oxisol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in some of these attributes may be related to crop residues, that is, from maize (straw) and pasture (forage mass), and residues from the excreta of grazing animals. Studies have reported the effect of these residues on soil (Bieluczyk et al, 2017; Carvalho et al, 2009; Deiss et al, 2016; Garcia et al, 2008; Silva et al, 2014; Zhou et al, 2020) but few of them have investigated the importance of sowing techniques for the implementation of ICLS in an Oxisol.…”
Section: Discussionmentioning
confidence: 99%
“…According to Loss et al (2012), ICLS tend to improve the SOC content of soil due to the combination of several factors such as dry mass, grass roots and shoots, plant residues from annual crops, and fertilization. In a three‐year experiment of an Oxisol, Bieluczyk et al (2017) found that ICLS increased SOM content in the topsoil layer, which is related to the increase in SOC, regardless of pasture height management.…”
Section: Discussionmentioning
confidence: 99%